Project on Human Development in Chicago Neighborhoods (PHDCN): Wechsler Intelligence Scale for Children-Revised, Wave 1, 1994-1997 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. The Wechsler Intelligence Scale for Children-Revised (WISC-R) was a general test of intelligence, which David Wechsler, the test's author, defined as "the global capacity of the individual to act purposefully, to think rationally, and to deal effectively with his environment." In keeping with this definition of intelligence as an aggregate of mental aptitudes or abilities, the WISC-R has traditionally consisted of 13 subtests divided into two parts, verbal and performance. For this study, the WISC-R included definitions of words only. It was administered to Cohorts 6, 9, 12, and 15.